What’s childhood asthma in French Guiana? A cohort study based on children referred for allergology consultations at the Cayenne hospital center - Maniassom, Chiméne; Defo, Antoine; De Blay, Frédéric; Elenga, Narcisse (Frontiers in Public Health, 2023)
Background. Asthma is a multifactorial chronic disease, whose most frequent etiology is allergy, especially to Blomia tropicalis. In French Guiana, the childhood prevalence of Blomia T sensitization is unkwown. The aim of this study was to determine the proportion of sensitization to Blomia T and other mites in asthmatic children, and to describe the characteristics of childhood asthma in French Guiana. Methods. A retrospective cohort study focused on children from 0 to 18 years of age, followed for asthma at the Department of Pediatrics of the Cayenne Hospital Center in French Guiana. All asthmatic children followed by the same paediatric allergist were systematically skin-tested with Bt total extract, and Bt-specific IgE tests were additionally performed to confirm specific sensitization. All follow-up variables were collected from medical records. The outcome was sensitization to Blomia tropicalis and other allergens, and the explanatory variables were those of asthma follow-up. Patients were categorized into Blomia tropicalis sensitization yes/no. Logistic regression analysis was used to assess the relationship between follow-up variables and the outcome. Results. 302 patients were followed: 177 cases of allergic rhinitis, 135 allergic conjunctivitis, 105 atopic dermatitis, 153 food allergy, and 14 cases of drug allergy. Poly-allergy (respiratory, food, skin, and medicinal) was present in 239 children. There were 158 children followed for asthma, of whom 103 (65%) were sensitized to Blomia tropicalis. The median age of the asthmatic children sensitized to Blomia tropicalis was 7 years, and 3 years for those who were not sensitized (p < 0.001). Among the girls (n=58), 67% were sensitized to Blomia; 97 (92%) asthmatic children co-sensitized to Blomia tropicalis, Dermatophagoides pteronyssinus, and Dermatophagoides farinae. Multivariate analysis showed that the childhood asthma in French Guiana is characterized by a median age of 7 years (p < 0.001), a high prevalence of Blomia tropicalis (p < 0.001), co-sensitization to other mites (p < 0.001), and a high prevalence of co-sensitization to cockroaches (p = 0.006). The area under the ROC curve was close to 0.9, confirming the quality of our model. Conclusion. In French Guiana, asthma is characterized by a high prevalence of Blomia tropicalis sensitization.